REPRESENTASI KEPEMIMPINAN PADA LUKISAN PRABU UDAYA KARYA I KETUT BUDIANA - Dwi Pradita, Agus Multazam; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTRACT The characteristic of leadership intensely affecting the general welfare in that area. A representation of the nature of leadership can be seen in a painting by I Ketut Budiana displayed in the Auditorium Widya Sabha Universitas Udayana. The painting was tell stories about Journey of Prabu udayana since was born then began to reign King of Bali, until the moksa process.  This study aimed to understand representation of leadership to the Prabu Udayana painting by I ketut Budiana. The research was used qualitative approach with the method of Charles sanders Pierce Semiotics analysis . A source of primary data on this research was Prabu udayana Painting by I ketut Budiana. The result of this research, eight of fourteen canvas representated characteristic of leadership with four the concept of Hindu Leadership on the majapahit era known as Catur Kotamaning Nrpati refers with four main requirement that should be owned by a leader. The four main requirements are Jñana Wisesa Suddha (a leader must have a virtuous knowledge) Kaprahitaning Praja (a leader must showed compassion to people), Kawiryan (a leader must be brave and fight for right and  justice), dan Wibawa (a leader must have a power to people). Keywords: Ketut Budiana, Painting, Prabu Udayana, Representation of Leadership, Semiotics.